Incidence of stalk rot and grain rot in maize - Wordell, João Américo (2020)
Stalk rot (SR) and grain rot (GR) occur frequently in crops of maize, causing losses to farmers. The objectve of this study was to evaluate the incidence of SR and GR in six cultvars of maize during the early cycle, conducted in two diﬀerent sowing dates and to identfy the fungal species associated. The experiment was carried out during the 2007-2008 growing season, in no-tll system and monoculture area, having rye as the preceding winter crop. The experiment was arranged in randomized complete blocks, distributed in a factorial 6 x 2 (six corn cultvars x two sowing dates), with four replicatons. The treatments were: S1 (P30F53/70,000 pl/ha), S2 (AGN 30A09 / 65,000 pl/ha), S3 (CD 308/60,000 pl/ha), S4 (DKB 240/70,000 pl/ ha), S5 (open-pollinated variety SCS154 Fortuna/50,000 pl/ha) and S6 (open-pollinated variety SCS155 Catarina/50,000 pl/ha). The treatments had diﬀerent behaviors on the incidence of SR and GR. Treatments S1 and S4 had a higher incidence of SR and treatments S1 and S6 had the highest percentage of GR. Fungi Stenocarpella maydis and Fusarium vertcillioides were the mainpathogens to cause SR while Fusarium vertcillioides was predominant in the GR